Aloe vera Gel Ameliorates Fat-Rich and High Fructose (FRHF) Diet-Induced Pancreatic and Splenic Damage in Mice - Nathan Isaac Dibal; Zainab Muhammad Goni; Martha Orendu Oche Attah; Umar Imam; Muhammad Abdullahi; Muzammil Bashir; Usman Adam; Fatima Aisami; Mohammed Shuwa; Sunday Joseph Manye; Madu Nom Gadzama; Musa Samaila Chiroma; Helga Bedan Ishaya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
High-fat diet alone or in combination with high fructose has been known to induce diabetes, obesity, hypertension, and immune dysfunction. The study evaluates the role of Aloe vera in fat-rich and high fructose diet-induced (FRHFD) hyperglycemias in addition to testicular and splenic morphology in mice. Twenty BALB/c Mice were randomly distributed into four groups (n=5). The groups were fed on a normal diet, FRHFD, FRHFD + 10 g A. vera, and FRHFD + 20 g A. vera for 10 weeks. All the mice were sacrificed a day after the 10 weeks of treatment. The result showed that mice fed on FRHFD plus A. vera had a significantly lower (p<0.05) blood glucose level relative to the FRHFD-fed mice. The mice fed on FRHFD plus A. vera had a significantly lower (p<0.05) blood glucose level relative to the FRHFD-fed mice. Aloe vera was found to ameliorate FRHFD-induced pancreatic islet and acini damage. It also prevented distorted lymphoid cells and testicular damage induced by FRHFD. Aloe vera prevents hyperglycemia and protects pancreatic islets in FRHFD-fed mice. It further prevents immune dysfunction and protects against testicular damage. Hence, A. vera supplementation could be an alternative and/or complementary therapy for hyperglycemia-related disorders.